Sexual Harassment In Academia: Economic And Legal Implications - Rahim, Rohani Abdul; Awal, Noor Aziah Mohd; Hamid, Bahiyah Abdul; Mohamed, Mohamad Hidir (Universiti Sains Malaysia, 2016)
Field of academia has faced allegations made by students, workers and educators with problem of sexual harassment. Most of the time the higher education institution have either ignored the problem or coping with it quietly (privately) or by quieting student victims of such harassment. Definition and attitudes towards sexual harassment is among the problem. Most of the definitions include the act of power over the victims, the unwanted behavior according to the victims, negative harms such as distress or interference with activities and many other different types of specific behavior. Some of the theoretical foundations related to sexual harassment include power relations, gender, environmental, organizational and individual influences. Conflict and role theory also closely related to understanding sexual harassment behavior. The types of sexual harassment commonly identified are; (a) sexist remarks or behavior: (b) inappropriate and offensive, but sanction-free sexual advances: (c) solicitation of sexual activity by promise of rewards: (d) coercion of sexual activity by threat of punishment; and (e) sexual crimes. Sexual harassment may contribute to an undetermined extent to many aspects of women's employment experience, including absenteeism, turnover, productivity rates and work motivation, job dissatisfaction, and unemployment. This paper intends to identify the legal definition, the forms and types of sexual harassment that took place in the academia, some of the coping strategies adopted by the victims, the study and work relate as well as the economic and legal implications that arise out of this victimization practiced by the perpetrators. On this basis, higher education institutions should clearly state their policies on the prohibition of sexual harassment, avenues of complaint, and sanctions for incidents, and suggests comprehensive sexual harassment law to be enacted to deal with sexual harassment that encroach in every sphere of life so that some kind of legal protection can be offered at any time.